Tantangan Tenanga Kesehatan dalam Mengelola Risiko K3 di Puskesmas Blang Geulumpang - Mansura Feby Amanda; Mira Ayu (Pusat Riset dan Inovasi Nasional, 2025)
Health workers in managing Occupational Safety and Health (K3) risks at the Blang Geulumbang Health Center. The aspect of K3 is important to protect health workers, patients, and the community from occupational risks, but its implementation often faces obstacles. Key findings include limited personal protective equipment (PPE), suboptimal management of medical waste, and lack of regular training and supervision. High workload and low budget allocation are also obstacles. This study recommends increasing training, providing adequate facilities, and strengthening managerial policies to support the implementation of K3 more effectively. The implementation of this strategy is expected to create a safer work environment and improve the quality of public health services.